2003
DOI: 10.5713/ajas.2003.269
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transglutaminase Modifies Gel Properties of Porcine Collagen

Abstract: We studied the gel properties of porcine collagen with microbial transglutaminase (MTGase) as a catalyst. A creep meter was used to measure the mechanical properties of gel. The results showed samples with high concentration of MTGase gelled faster than those with a low concentration of MTGase. The gel strength increased with incubation time and the peaks of breaking strength for 0.1, 0.2 and 0.5% MTGase were obtained at 40, 20 and 10 min incubation time, respectively. According to SDS-PAGE, the MTGase was suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Collagen I is a substrate of transglutaminase that introduces e-(g-glutamyl) lysine cross-links into its molecule at 37 C. 29,30 Fibroblast attachment, spreading and proliferation is enhanced on collagen polymerized as a result of transglutaminase treatment. 31 Collagen can also be crosslinked by 0.2% glutaraldehyde and used as a matrix for cell culture.…”
Section: Collagen Matrix Modelsmentioning
confidence: 99%
“…Collagen I is a substrate of transglutaminase that introduces e-(g-glutamyl) lysine cross-links into its molecule at 37 C. 29,30 Fibroblast attachment, spreading and proliferation is enhanced on collagen polymerized as a result of transglutaminase treatment. 31 Collagen can also be crosslinked by 0.2% glutaraldehyde and used as a matrix for cell culture.…”
Section: Collagen Matrix Modelsmentioning
confidence: 99%
“…We again observe the phenomena of decreasing R CT in the Nyquist plot, similarly to what occurred with the amylase and lipase alone. The 4-fold reduction in degradation rate may be alleviated by modifying the film to prevent non-specific binding, such as with the use alternative crosslinkers (microbial transglutaminase has shown to be effective), inhibitors (orlistat or tendamistat for lipase and amylase, respectively) or with more specific film materials to trypsin (i.e., poly-L-lysine) [27][28][29]. Overall, however, the experiments conducted above allowed us to observe the impacts of these enzymes on the impedance of these gelatin films, and it appeared that the presence of trypsin, rather than the non-specific enzymes, is responsible for inducing these changes in impedance over the film-coated sensors.…”
Section: Enzyme Mixture Impedance Resultsmentioning
confidence: 99%
“…Limited range of elasticity (100 Pa -2 kPa) adjustable by varying pH, gelation temperature, and collagen concentration [330] Increase of stiffness by crosslinking, [200] ultracentrifugation, [201] gel compression, [202] evaporating the solvent [203] or chemical modification [204] Mild stiffness adjustment via transglutaminase-mediated crosslinking [198] and MMC [207c] Suitable for embedding cells Self-assembling Smooth muscle cells, [184] MSC differentiation, [185] adipocytes culture and differentiation, [186] epithelial growth and branching of several organs, 332] tumor modeling, [191][192][193][194] angiogenesis [196,197,333] Human and murine intestinal organoid cultures [209,210] Murine stomach organoid, [209d] modeling PKD cystogenesis [211] Biopolymer [339] Mimics the mechanical properties of neonatal hearts Electrostatically complexes positively charged growth factors (e.g., bFGF, SDF-1, VEGF) [340] Contains target sequences of matrix metalloproteinases (MMP) rendering it degradable Cardiac grafts based on fetal rat ventricular muscle, [214] angiogenesis, [215a] colonoids, [223] cardiac fibrosis [339] Biopolymer-based hydrogels: Hyaluronic acid From rooster combs, shark skin, bovine eyeballs, or human umbilical cords [335] Animal-free produc- BMP, [343] NGF, SDF-1α) [342] Allows for hyaluronidases-mediated remodeling [267] or for degradation by reactive oxygen species [346] Engineered MMP degradation sites allow further degradation Undifferentiated hESC growth, [344] bone and cartilage engineering, [345] neural differentiation,…”
Section: Reconstituted Fibrillar Structurementioning
confidence: 99%
“…[ 196 ] It has been shown that a change in collagen I gel‐stiffness alters endothelial cell spreading, angiogenic sprouting and glycation products. [ 197 ] Collagen I is a substrate of transglutaminase and can thus be cross‐linked through ϵ‐(γ‐glutamyl) lysine, [ 198 ] which resulted in enhanced fibroblast attachment, spreading and proliferation. [ 199 ] Collagen I gels can also be tuned in stiffness by cross‐linking with glutaraldehyde, [ 200 ] ultracentrifugation, [ 201 ] gel compression, [ 202 ] evaporating the solvent, [ 203 ] or further chemical modification methods.…”
Section: Engineering Cell‐ and Tissue‐instructive Hydrogel Materialsmentioning
confidence: 99%